Dynamic Instability of Plates Made of Nonlinear Viscoelastic Materials - Cederbaum, G.; Touati, D. (Engineering Transactions, 1996)
The dynamic stability analysis of isotropic plates made of a nonlinear viscoelastic material is performed within the concept of the Lyapunov exponents. The material behaviour is modelled according to the Leaderman representation of nonlinear viscoelasticity. The influence of the various parameters involved on the possibility of instability to occur is investigated. lt is also shown that in some cases the system is chaotic.